2015
DOI: 10.3139/217.2984
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Numerical Simulation of Void and Warpage in Glass Fiber Reinforced Molded Chunky Parts

Abstract: The aim of this paper is to determine the reason for the large warpage of an injection molded chunky part made of glass fiber reinforced polyamide 6. State of the art commercial 3D injection molding simulation software was used to predict the warpage of the part. While the simulation predicted a product virtually free of warpage the molded parts showed a large deformation. Several molding experiments and X-ray computed tomography (μCT) scans of the moldings have been performed to figure out the reason for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The standard states that this measurement technique is only applicable for short fiber‐reinforced materials. Although this standard exists, only one publication was found that specifically analyzed the fiber length according to this standard and cited it . Nevertheless, most measurement procedures in the field are similar to the ISO:22314 standard.…”
Section: State‐of‐the‐artmentioning
confidence: 99%
“…The standard states that this measurement technique is only applicable for short fiber‐reinforced materials. Although this standard exists, only one publication was found that specifically analyzed the fiber length according to this standard and cited it . Nevertheless, most measurement procedures in the field are similar to the ISO:22314 standard.…”
Section: State‐of‐the‐artmentioning
confidence: 99%
“…The voids, being undetectable by visual observation, may exert the most detrimental effect on the mechanical performance of injection-moulded components, weakening their capacity to withstand the loads while in service and leading to crack initiation and failure [ 10 , 11 , 12 ]. The influence of the excessive shrinkage, in chunky plastic parts moulded from fiber reinforced composites, was highlighted as the main cause of the occurrence of voids and warpage by Kleindel et al [ 13 ]. Their conclusions were corroborated by the findings of Vaxman et al for thick-walled, injection-moulded Noryl (polyphenylene-oxide/polystyrene) components [ 14 ].…”
Section: Introductionmentioning
confidence: 99%